Serum levels of 25(OH)D are not associated with venous thromboembolism in the elderly population - Andro, Marion; Delluc, Aurélien; Moineau, Marie-Pierre; Tromeur, Cécile; Gouillou, Maelenn; Lacut, Karine; Carré, Jean-Luc; Gentric, Armelle; Gal, Grégoire Le (Thrombosis and Haemostasis, 2016)
The prevalence of both vitamin D deficiency and venous thromboembolism (VTE) is important in the elderly. Previous studies have provided evidence for a possible association between vitamin D status and the risk of VTE. Thus, we aimed to investigate the association between vitamin D levels and VTE in the population aged 75 and over included in the EDITH case-control study. The association between vitamin D status and VTE was analysed. We also analysed the monthly and seasonal variations of VTE and vitamin D. Between May 2000 and December 2009, 340 elderly patients (mean age 81.5 years, 32 % men) with unprovoked VTE and their controls were included. The univariate and multivariate analysis found no significant association between serum levels of vitamin D and the risk of unprovoked VTE. In the unadjusted analysis, a higher BMI was statistically associated with an increased risk of VTE (OR 1.09; 95 % CI 1.05–1.13) whereas a better walking capacity and living at home were associated with a decreased rate of VTE: OR 0.57; 95 % CI 0.36–0.90 and 0.40; 95 % CI 0.25–0.66, respectively. Although not significant, more VTE events occurred during winter (p=0.09). No seasonal variations of vitamin D levels were found (p=0.11). In conclusion, in contrast with previous reports our findings suggest that vitamin D is not associated with VTE in the elderly population.
Keywords: Vitamin D; venous thromboembolism; aged; risk factors; case-control study